O paradigma pós-humano e os riscos da despolitização da governação - João Maia (Cidades, Comunidades e Território)
This article’s main objectives are to characterize the logics that underlie governance framed within the post-human paradigm, to emphasize the risks of this type of governance and to mention the organizational principles for alternative governance. The text’s approach takes as its central issue the development of automation technologies and the internet of things and their applications in society and the environment. Given the political and economic logics of current globalization, the need for participatory and representative citizenship at different levels of political decision-making is defended, including in matters of sharing and transmission of scientific-technological knowledge.